INTEGRASI MONOLOG INTERIOR DAN INTERTITLE DALAM BAHASA FILM: TELAAH PERSPEKTIF ESTETIKA TERHADAP FILM ADAPTASI “HUJAN BULAN JUNI” (2017) - Nashrullah Ali Fauzi; Nurbaiti Fitriyani (CrossOver, 2022)
The adaptation of literary works to film is not new in this era. After undergoing several transformations from poetry to musicals, comics, graphic-novels, and novels, Hujan Bulan Juni as a literary work was then adapted into the film art with the same title. This research focuses on the film Hujan Bulan Juni (2017) directed by Reni Nurcahyo Hestu Saputra which was adapted from the text of the novel and poem Hujan Bulan Juni written by Sapardi Djoko Damono. Although there have been changes from literary works to films, film directors certainly want to maintain fidelity in the works even though this is not possible, because both have different mediums and have gone through different interpretation processes. In the end, it becomes understandable if there are so many elements that are removed or even added in a film adaptation. However, there are elements that actually change the point of view of the story and obscure the aesthetics of the film so that it is disturbing, namely the interior monologue and intertitle. The use of these two elements affects the essence of cinema which is projected through audio and visual, in which the film has a medium specification in the form of moving images. In this study, the researcher tries to describe what elements are removed or added by the director from the novel to the film and how they affect the adaptation work. To find out the characteristics of each of these mediums, it is necessary to conduct a comparative study. One way to find out the comparison, in this study using an intertextuality approach with microcosmic and macrocosmic methods. The result shows that the film adaptation does not maintain the fidelity. Interior monologue that appears a lot in the novel is mostly removed and the intertitle is excessively added.